Addictions and risk behaviors in adolescence: a systematic review and qualitative analysis - Simón Márquez, María del Mar; Fernández Gea, Silvia; Molero Jurado, María del Mar; Molina Moreno, Pablo; Pérez-Fuentes, María del Carmen (Frontiers in Psychology, 2025)
IntroductionSubstance abuse and behavioral addictions among adolescents represent a growing public health concern, with significant implications for their physical, mental, and social development. This systematic review aimed to identify the most commonly used substances and prevalent addictive behaviors in this population.MethodsA comprehensive search was conducted across multiple scientific databases to select studies published between 2018 and 2023. Documents were analyzed qualitatively using the ATLAS.ti Web tool to identify patterns in the use of substances (alcohol, tobacco, cannabis, and cocaine) and behavioral addictions (problematic use of the internet, video games, gambling, smartphones, and social media).ResultsAfter the systematic and manual selection process, a total of 41 research studies were obtained. Findings indicate that alcohol and tobacco are the most commonly used substances among European adolescents, with early onset linked to a higher risk of addiction. Excessive use of the internet and social media was also identified as a major concern, negatively impacting mental and social health. Video game and gambling addictions showed high prevalence rates, influenced by socioeconomic and family-related factors.ConclusionThese findings highlight that addictive behaviors in adolescents are multifaceted and influenced by biological, social, and environmental factors. There is a clear need for comprehensive prevention strategies that address both substance use and behavioral addictions to mitigate their impact on adolescent health.